Le fort de Verdun localisé - Dubeau, Pierre (Les Argoulets, 2024)
Keywords: Forts; Verdun

La cavalerie de Montréal. L'histoire du Royal Canadian Hussars (Montreal) - Kellett, Anthony; Linton, Steven; Cochrane, John (L'institut de cavalerie de Montréal, 2024)
Keywords: Combat; Milice

La vie de John Elsdale Molson - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont

DOHERTY, CHARLES JOSEPH - Glassford, Larry A. (Dictionnaire biographique du Canada, 2023)

CULLEN, MAURICE GALBRAITH - Prioul, Didier (Dictionnaire biographique du Canada, 2022)

BRAINERD, THOMAS CHALMERS - Cloutier, J.-Roger (Dictionnaire biographique du Canada, 2021)

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

La mutation vers un espace urbain moderne. Le projet de démantèlement des fortifications de Montréal - Beauchamp-Monfette, Joel (Cap-aux-Diamants, 2020)
issued: 2020-24-00
Keywords: Fortifications

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Continentals and Coureurs De Bois: The American Invasions of Canada and Illinois in the Revolutionary War - Keck, John D. (Sam Houston State University, 2018)
Keywords: Américains; Gouverneurs

Daily Life in Montreal during the Eighteenth Century - Turcot, Laurent (Montreal: The History of A North American City, 2018)
Keywords: Auberges; Cabarets; Danse; Hôtellerie; Marchés; Rues; Théâtre; Vêtements

Careful Coexistence: The Canadians and British in Montreal prior to 1800 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Américains; Britanniques; Gazette Littéraire de Montréal; Gouverneurs; Loyalistes; Marchands; Mesplet; Fleury; Protestants; Écossais

Montréal 1760: reddition de la Nouvelle-France - Lessard, Rénald (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Britanniques; Capitulation; Français

Montréal sous l’emprise des révolutionnaires américains - Monette, Pierre; Delisle, André (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Américains

Une ville fortifiée - Bélanger, Christian (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts

150 ans d’histoire militaire au centre-ville de Montréal - Joly, Diane (Revue militaire canadienne, 2016)
issued: 2016-24-00
Keywords: Dominion (square); Guerre; Monuments; Places publiques; Squares

Au temps où l'île Sainte-Hélène était militaire - Royer, Martin (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts; Île Sainte-Hélène

FYEN, ALFRED - Auger, Jean-François (Dictionnaire biographique du Canada, 2015)

With Thought and Faith: Henri Bourassa and the Great War - Keelan, Geoff (Worth Fighting For: Canada’s Tradition of War Resistance from 1812 to the War on Terror, 2015)
Keywords: Bourassa; Henri; Devoir (Le); Guerre

100 tonnes d'explosifs stockés sur l'avenue Dunlop! Intolérable! - Lester, Normand (Mémoire vivante, 2015)
issued: 2015-24-00/2016-24-00
Keywords: Armes; Forts; Rébellions

Louis-Joseph Papineau. Les débuts, 1808-1815 - Ostiguy, Raymond; Aubin, Georges (Éditions Histoire Québec, 2015)
Keywords: Avocats; Députés; Guerre; Milice; Papineau; Louis-Joseph

''It was impossible to make any further resistance'': The Final Act Plays Out before Montreal - Cubbison, Douglas R. (All Canada in the hands of the British: General Jeffery Amherst and the 1760 campaign to conquer New France, 2014)
Keywords: Capitulation

La gouvernance municipale avant la municipalité : Montréal, 1760-1840 - Fyson, Donald (La gouvernance montréalaise : de la ville-frontière à la métropole, 2014)

"Fidèle à Dieu, à la France, et au roi" : les retraites militaires de La Chapelle et de Beaujeu vers la Louisiane après la perte du Canada 1760-1762 - Gagné, Joseph (Université Laval, 2014)
Keywords: Capitulation

Charles-Madeleine Youville-Dufrost, prêtre et sa mère, Marguerite d'Youville - Mathieu, Jacques (Vivre la Conquête à travers plus de 25 parcours individuels, 2013)
Keywords: Dufrost de Lajemmerais; Marie-Marguerite (Youville; Marguerite d')

Lacorne Saint-Luc: l'odyssée d'un noble, 1711-1784 - Saint-Pierre, Marjolaine (Septentrion, 2013)
Keywords: Fourrure; Guerre; La Corne; Luc de (La Corne Saint-Luc ou Saint-Luc de La Corne); Marchands; Noblesse

An Examination of the Coverage of the War of 1812 in the Montreal Gazette, 1812-1815 - Perrone, Julie (Canadian Issues, 2012)
issued: 2012-23-00
Keywords: Guerre; Montreal Gazette

Moeurs, sociabilités et mentalités montréalaises: la vie quotidienne dans la ville au XVIIIe siècle - Turcot, Laurent (Histoire de Montréal et de sa région, 2012)
Keywords: Auberges; Cabarets; Danse; Hôtellerie; Marchés; Rues; Théâtre; Vêtements

Cohabiter avec et contre l'autre: Canadiens et Britanniques à Montréal avant 1800 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Américains; Britanniques; Gazette Littéraire de Montréal; Gouverneurs; Loyalistes; Marchands; Mesplet; Fleury; Protestants; Écossais

La guerre de 1812: Journal de Jacques Viger - Viger, Jacques; Andrès, Bernard (Les Presses de l'Université Laval, 2012)
Keywords: Maires; Viger; Jacques

The British Garrison and Montreal Society, 1830-1850 - Vineberg, Robert (Canadian Military History, 2012)
issued: 2012-24-00
Keywords: Armée; Britanniques; Garnison

The Colonial Landscapes of the Early Town - Coates, Colin M. (Metropolitan Natures: Environmental Histories of Montreal, 2011)

Le radicalisme tory à travers le prisme du Montreal Herald et la mobilisation des milices dans le district de Montréal (1834-1837) - Deschamps, François (Université du Québec à Montréal, 2011)
Keywords: Milice; Rébellions

The Surrender of Montreal to General Amherst de Francis Hayman et l'identité impériale britannique - Turcot, Laurent (Mens, 2011)
issued: 2011-23-00
Keywords: Capitulation; Guerre; Peinture

Jacques Viger et Joseph Mermet: naissance d’un écrivain (1814-1828) - Andrès, Bernard (Les Cahiers des dix, 2010)
Number: 64
Keywords: Maires; Viger; Jacques; Écrivains

"Monseigneur, pardonnez-moi parce que j'ai péché": la régulation de la dissidence au sein du clergé canadien, au moment de l'invasion américaine de 1775-1776 - Turgeon, Charles (Université de Montréal, 2010)
Keywords: Américains; Chartier de Lotbinière; Eustache; Floquet; Pierre-René; Huet de La Valinière; Pierre

Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (VLB Éditeur, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger; Jacques

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey; Daniel; Émeutes

Le fort et les poudrières du complexe militaire de l'île Sainte-Hélène - Royer, Martin (Université Laval, 2009)
Keywords: Armes; Fortifications; Forts; Île Sainte-Hélène

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet; Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard; Valentin; Journalistes; Librairie; Mesplet; Fleury

Le Roi, l'Église et la guerre: la prédication à Montréal au moment de la conquête (1750-1766) - Décary, Simon (Université de Montréal, 2008)
Keywords: Communautés religieuses; Sulpiciens

Les Pointeliers en guerre - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Armée; Guerre; Milice; Pointe-aux-Trembles; Quartiers

La stratégie lors de l'affrontement anglo-américain au Canada (1775-1776). Objets politiques et objectifs militaires - Nadeau, Charles André (Université Laval, 2008)
Keywords: Américains; Armée; Britanniques

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières; Pierre

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (University of British Columbia Press, 2006)
Keywords: Guerre; Quartiers; Verdun

A Man's a Man because of That: The Scots in the Canadian Military Experience - Klepak, H. P. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Armée; Écossais

WILSON, ERASTUS WILLIAM - Gagnon, Jean-Pierre (Dictionnaire biographique du Canada, 2005)

RODDICK, sir THOMAS GEORGE - Hanaway, Joseph (Dictionnaire biographique du Canada, 2005)

La milice du district de Montréal, 1787-1829: essai d'histoire socio-militaire - Lépine, Luc (Université du Québec à Montréal, 2005)
Keywords: Milice

MEREDITH, sir HENRY VINCENT - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Number: 75
Keywords: Guerre; Lachine; Émeutes

VALLÉE, CHARLES-AMÉDÉE - Tremblay, Marie J. (Dictionnaire biographique du Canada, 2005)

James McGill of Montreal : citizen of the Atlantic world - Cooper, John Irwin (Borealis Press, 2003)
Keywords: Autochtones; Fourrure; Marchands; McGill; James

The Last French and Indian War: an Inquiry Into a Safe-Conduct Issued in 1760 that Acquired the Value of a Treaty in 1990 - Vaugeois, Denis (McGill-Queen's University Press et Septentrion, 2002)
Translators: _:n41953
Keywords: Autochtones; Français

L'organisation de la milice de la région montréalaise de 1792 à 1837: de la paroisse au comté - Dion, Dominique; Legault, Roch (Bulletin d'histoire politique, 2000)
issued: 2000-24-00/2000-21-00
Keywords: Milice